2021
DOI: 10.18632/aging.202679
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-95-3p serves as a contributor to cisplatin resistance in human gastric cancer cells by targeting EMP1/PI3K/AKT signaling

Abstract: MicroRNAs (miRNAs) are thought to be involved in the development of cisplatin (DDP) resistance in gastric cancer (GC). Using RNA sequencing analysis (RNA-seq), we found that miR-95-3p is associated with DDP resistance in GC. We discovered that miR-95-3p is highly expressed in DDP-resistant GC tissues and cell lines (SGC7901/DDP and AGS/DDP). Furthermore, results from the BrdU and MTT assays indicated that miR-95-3p promotes GC cell proliferation. Additionally, data from transwell chamber assay, wound healing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…EMP1 has moved into the limelight in these tumor entities, where its expression is controversial in multiple cancer types; however, its expression and function are contradictory. A previous study has corroborated that EMP1 serves as a promising oncogene and is obviously downregulated in tumors and can enhance cell cytotoxicity in various cancer cells [ 35 ]. The underlying mechanisms of EMP1 ability in inducing ferroptosis have not been elucidated.…”
Section: Discussionmentioning
confidence: 92%
“…EMP1 has moved into the limelight in these tumor entities, where its expression is controversial in multiple cancer types; however, its expression and function are contradictory. A previous study has corroborated that EMP1 serves as a promising oncogene and is obviously downregulated in tumors and can enhance cell cytotoxicity in various cancer cells [ 35 ]. The underlying mechanisms of EMP1 ability in inducing ferroptosis have not been elucidated.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, c-Myc inversely regulates the expression of miR-567, leading to the formation of a miR-567-PIK3AP1-PI3K/AKT-c-Myc feedback loop (37). Ni et al found that miR-95-3p activates the PI3K/AKT signaling pathway by upregulating the expression of p-PI3K and p-AKT, leading to the enhancement of CDDP resistance of GC (76). PTEN is a key negative regulator of the PI3K/AKT signaling pathway (121).…”
Section: Mirnas Regulate the Drug Resistance Of Gc By Targeting Signaling Pathwaysmentioning
confidence: 99%
“…Ni et al. found that miR-95-3p activates the PI3K/AKT signaling pathway by upregulating the expression of p-PI3K and p-AKT, leading to the enhancement of CDDP resistance of GC ( 76 ). PTEN is a key negative regulator of the PI3K/AKT signaling pathway ( 121 ).…”
Section: Implication Of Mirnas In Gc Drug Resistancementioning
confidence: 99%
“…A large number of bioinformatics studies also show that miR-552-3p can be used as a biomarker for diagnosis and treatment of CRC [22]. Using RNA sequencing analysis (RNA-seq), miR-95-3p is linked to cisplatin resistance in gastric cancer, increasing the PI3K/Akt pathway [23,24]. Notably, to better understand the mechanisms of these miRNAs involved, we need further studies for their roles in CRLM.…”
Section: Construction Of Ppi and Dems-hubgenes Networkmentioning
confidence: 99%